The effect of violence during mass uprisings on the duration of the democratization process and inclusiveness in elections - Hussein, Gehad (AUC Knowledge Fountain, 2017)
The democratization process of countries all over the world after mass uprisings differs greatly. Some countries are confronted with extreme violence, while others remain peaceful. This thesis examines whether the amount of violence during mass uprisings leads to a longer democratization process and less inclusive elections in terms of voter base. It looks at the revolutions of 1989 in Eastern Europe which brought down the Communist bloc. The repercussions of the presence or lack of violence during the mass uprisings on the behavior of the population in each country is visible until this very day – with Romania and Bulgaria still struggling from subtle, but deep-rooted internal conflicts and discomfort with the concept of democracy, and Hungary, Poland, the Czech Republic and Slovakia’s significant progress in the democratization process and gradual increase of substantially embracing democratic values.